KEDUDUKAN HUKUM PEMBANTUAN / PENEMPATAN OPERATOR RTGC PT. PELINDO II (PERSERO) DI PT. JAKARTA INTERNATIONAL CONTAINER TERMINAL (JICT) BERDASARKAN UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS PUTUSAN PHI No: 137/PDT.Sus-PHI/2017/PN.JKT.PST) - Roder BA Sihotang (JURNAL HUKUM STAATRECHTS, 2018)
ABSTRACT THE  POSITION OF  LAW  THE  POSITION  IN OPERATOR RTGC  PT. PELINDO II (PERSERO) IN PT. CONTAINER TERMINAL INTERNATIONAL ENERGY JAKARTA (JICT) BASED ON CONTATUTION NO. 13 YEAR 2003 ABOUT ENERGY WORKERS (STUDI CASE IN DECISION PHI NO.137/PDT.SUS-PHI/2017/PN.JKT.PST)  As the development country, Indonesia has strong, wishes for doing the contruction especially in economy, for the while, on of the way for ever body in getting a job is doing as the formal or informal. Athough this case very a pity while be a entrepreneur to do the protest to be againt his own power workers, the which is done by PT. Container Terminal International Jakarta as a accuser to be against labour united of PT. Container Terminal International Jakarta with the teory sketch fair and prosperity teory, and also to use normative yuridis approach. This research in studying with using library study to use primary law material as the rule of legislation, secondary law material tertier like company, law literature. The law of power worked and the law material tertier like the opinion of the experts, law dictionary. The result of this research can be making conclusion that, the finishing of positive law in Indonesia for helping or to make the man on the right place as operator RTGC in PT. PElindo II (PErsero) in PT. Container Terminal International Jakarta are to submit protest at 17 Mei 2017 at court. The relationship industrial central Jakarta for the eases which are not giving the fair for the worker are happening the dismissal as a side without any the mistakes and to be caused so that must be gotten become miss receive or miss accept until all become lost. Happening the workers mutation for active man in workers organization workers so the concentration seatter everwhere, so the organization workers become minus or the weakness to struggle the qualification of the workers. The judge consideration at the definite PHI No: 137/PDT.Sus-PHI/2017/PN.JKT.PST are very very clear and fair for the workers PT.JICT which has done not fair by one in authority, because of the judge considenation one given the acceused protest about the definite the absolute judgement, and how to say that the judge has the relationship industry for in judiciary centre Jakarta don’t have the absolute judgement in this case. In the definite has been given the power for the labour united for the protest to be against and the grief the power workers in democration the power workers that had been wrong was.